State Terrorism and Human Rights Violations in Afghanistan: Post US Withdrawal Analysis - Aroosa Fatima (ASIAN Journal of International Peace & Security (AJIPS), 2024)
This article is built on the argument that the human right violations through state terrorism are harbinger of civil war, with an objective of emphasizing to shift the focus of academia on state terrorism in general, and particularly in Afghanistan. The massive human rights violations carried out through state terrorism during previous Afghan governments are contested but wildly accepted, suggests the correlation between state terrorism, human rights abuse and civil war. The methods of state terrorism including the mass killings, forced removal of opponents and ethnic-religious minorities, displacement, forced disappearance, ban on freedom of speech, and suspension of women’s rights, under current Afghan regime; combining with the feeble economy and return of Afghan refugees is turning security situation of Afghanistan into a catastrophe, which civil war can aggravate to the extreme and irreversible lengths. The lacking focus of academia on state terrorism is affecting the international community’s response to state based human rights abuses. Without classifying state terrorism as a heinous crime, it is impossible to force the international community to take action against this practice, safeguard fundamental rights and ensure peace.